Maternal and Foetal outcome in Cholestasis of Pregnancy - Sinha, Kavita; Pandey, Subhash; Das, C. R. (Journal of Nepalgunj Medical College, 2017)
Background: Obstetric cholestasis has been associated with an increased risk of preterm delivery, intrapartum meconium, foetal distress and intrauterine foetal death.Objectives: To know the perinatal outcome of cholestasis in pregnancy.Materials & Methods: This is a hospital based Observational study conducted in the department of Obstetrics & Gynaecology at Nepalgunj Medical College Teaching Hospital Kohalpur between August 2015 to January 2016.A total of 40 patients were included in the study with diagnosis of obstetric cholestasis. Data were recorded & analysed.Results: The study group of 40 mothers delivered 40 new born. Mean age group of women in the study was 24.9±5.5 years & 70% were primigravida. The mean gestational age at onset of pruritus was 30.33±4.24 weeks. The rate of caesarean section was 40%. Premature membrane rupture noted in 20% cases while 17.5% were postpartum haemorrhage. Regarding foetal outcome; meconium baby 32.5%, Intrapartum foetal distress 17.5%, preterm baby 10% while 37.5% were complication free. There was 2.5% of intrauterine foetal death, where pregnancy continued beyond 38 weeks. Thirteen new borns (32.5%) were admitted to neonatal intensive care unit.Conclusion: Cholestasis in pregnancy is high risk group with adverse perinatal outcomes.JNGMC Vol. 14 No. 1 July 2016, page: 32-35